Network meta-analysis of tuina or acupuncture in combination with adjunctive therapy for cervical spondylotic radiculopathy - Shengxiang Zhao; Jie Yang (Frontiers in Neurology)
BackgroundTuina and acupuncture therapy have been widely applied in patients with cervical spondylotic radiculopathy (CSR). This network meta-analysis (NMA) was carried out to compare the effects of tuina or acupuncture in combination with adjunctive therapy on the physical signs, symptoms, and clinical outcomes of patients with CSR.MethodRelevant studies were searched in PubMed, Web of Science, Embase, Cochrane, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang Data, and China Biology Medicine (CBM), up to June 15, 2023. Randomized controlled trials (RCTs) comparing tuina, acupuncture, or their combination with conventional Western medical adjunctive therapies were selected. Literature quality was assessed using the ROB2 tool, and statistical analyses were conducted using Stata SE15 and R 4.3.1.Results90 studies involving 8,612 participants were included. Compared to acupuncture alone, acupuncture + warm needle acupuncture (RR: 17.97; 95% CrI [1.98, 563.78]), acupuncture + cupping (RR: 15.84; 95% CrI [1.48, 538.41]), tuina + auricular acupuncture and conventional therapy (RR: 12.83; 95%CrI [1.31, 170.78]), acupuncture + moxibustion (RR: 8.55; 95% CrI [2.17, 40.28]), and acupuncture + warm needle acupuncture (RR: 8.62; 95% CrI [1.78, 50.25]) significantly improved the clinical response rate, with acupuncture + warm needle acupuncture exhibiting the best effect (SUCRA: 85.9%). Tuina (SUCRA: 75%) ranked highest in improving the cervical function of patients. Electroacupuncture + moxibustion and conventional therapy (SUCRA: 97%) was most effective in relieving pain. None of these therapies effectively improved patient physical signs.ConclusionNeedling + warm needle acupuncture, warm needle acupuncture + auricular acupuncture, and warm needle acupuncture + conventional therapy may better alleviate symptoms in patients with CSR. However, more well-designed multicenter, large-sample RCTs are needed to further analyze the findings from this study.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023443945, CRD42023443945.